Explaining Aid Project and Program Success: Findings from Asian Development Bank Interventions. (February 2017) - Feeny, Simon; Vuong, Vu
Highlights: This paper examines the determinants of success of aid interventions. The paper analyses a dataset of over 1, 600 projects and programs of the Asian Development Bank. Aid projects are more likely to be successful than programs. Interventions are less likely to be successful in the Pacific. Variables often used to determine aid allocations are found to have little power in explaining success. Summary: This paper contributes to the aid effectiveness literature by examining the determinants of aid project and program success. Both macro (country level) and micro (project level) determinants are considered. The paper employs a variety of econometric techniques to examine evaluation data for countries in the Asia-Pacific from the Asian Development Bank (ADB) for period 1970–2010. At the macro level, the rate of per capita income growth is positively associated with aid project and program success. Aid interventions are found to have a lower probability of success in the Pacific and, surprisingly, in countries with higher levels of democracy. There is little association between project and program ratings and the level of governance. At the micro level, projects are more likely to be successful than programs, as are larger aid interventions. Interventions which received less funding than anticipated, possibly due to capacity constraints, are found to have a lower probability of success. Despite these statistically significant findings, both macro and micro variables contribute very little to the explanatory power of models explaining the variation in project and program outcomes. The paper concludes that the ADB should reconsider its performance based aid allocation model.